Prevalence and risk factors of anti-tuberculosis drug-induced hepatitis in Malaysia - Omar, Ahmad Marzuki; Abdul Rani, Mohammed Fauzi; S, Ayoub; Musa, Kamarul Imran (Singapore Medical Association, 2008)
Tuberculosis (TB) affects onethird of the world’s population. Anti-TB drugs with isoniazid, rifampicin and pyrazinamide are very effective but they can cause hepatotoxicity. Many risk factors have been recognised. Data on prevalence of anti-TB drug-induced hepatitis as well as the contributing risk factors are scarce in Malaysia. This observational case control study was designed to look at the prevalence and the risk factors of drug-induced hepatitis in our population.